Upaya Menekan Penyakit Menular dan Tidak Menular melalui Pendekatan Edukasi Kesehatan Berbasis Herbal dan Pendampingan Latihan Fisik - Ysrafil, Ysrafil; Komara, Nisa Kartika; Hanasia , Hanasia; Pratika, Remi Ayu; Ahmad, Farah Fauziyah Radhiyatulqalbi (Jurnal SOLMA, 2025)
Background: Based on Indonesian Health Survey, Central Kalimantan has the highest prevalence of hypertension in Indonesia (40.7%). A similar situation occurs in Pahandut Seberang, In 2024, hypertension among top three most common diseases alongside respiratory tract infections and scabies, with 200, 290, and 190 cases out of 1,831 residents. The high incidence rate is influenced by excessive salt consumption, smoking, lack of physical activity, and geographical conditions prone to flooding. Recently, community has mostly used conventional drugs that cause side effects, while small number have tried herbal medicines, but their processing has not been appropriate. Method: To address these issues, our team implemented community service program consisting of education on hypertension, ISPA, and scabies, training on innovative herbal products, and physical exercise guidance (aerobic exercises, elderly exercises, and yoga) by involve of professional instructors. Results: The post-test results showed an increase in the cadres' understanding of educational material. Participants were also able to independently practice processing herbal plants into useful products (herbal tea, liquid soap, aromatherapy candles, and herbal creams) and demonstrate the physical exercises they had been taught. The community showed high enthusiasm, accompanied by appreciation and gratitude for the activities. In addition, the community service team teach cadres in obtaining PIRT (Traditional Food Product Registration) to support the sustainability of herbal products. Conclusion: The program successfully improved the knowledge, skills, and independence of cadres in processing herbs and performing physical exercises, thereby becoming strategic to prevent and reduce the incidence of communicable and non-communicable diseases in Pahandut Seberang